Cognitive theories and users of communication (A study in the behavioral interpretation of individuals) (Journal of the College of Basic Education, 2022)
It is certain that there are features specific to the means of communication, and thanks to them, it has become a distinguished influence on the lives of those who are exposed to it. It appears simultaneously and another percentage will have long-term and cumulative subsequent effects related to behavior.